Neuroimaging and behavioral investigation of declarative memory in South African children prenatally exposed to alcohol - Lewis, Catherine Elizabeth (Department of Psychology, 2018)
Prenatal alcohol exposure (PAE) is associated with a range of physical, growth, and neurobehavioral deficits characteristic of individuals with fetal alcohol spectrum disorders (FASD). Although declarative memory impairment is a key feature of the neurocognitive profile of FASD, the mechanisms underlying this deficit require further clarification. The aim of this cross-sectional research was to examine, both directly and indirectly (via bottom-up and top-down processes), a critical cognitive mechanism that supports successful declarative memory functioning (viz., memory encoding), in children with FASD. Data were collected from a sample (N = 88) of South African children with and without PAE. In Study I, I used a blocked design functional magnetic resonance imaging (fMRI) paradigm to investigate neural activation during visual perception, a lower-order cognitive process essential to memory encoding. The task elicited bilateral category-specific activation during the visual perception of objects and scenes in all participants. The absence of between-group differences suggests that functional recruitment of brain regions during basic visual perception is less susceptible to the effects of PAE than during higher-order processes supporting memory encoding. In Study II, I used an event-related fMRI paradigm to investigate neural activation during memory encoding itself. All participants demonstrated similar memory performance accuracy and recruited extensive bilateral networks during memory encoding. However, participants with a diagnosis of fetal alcohol syndrome (FAS) or partial FAS (PFAS) activated additional regions associated with attentional function. Within the FAS/PFAS group, higher exposure levels were associated with smaller activation increases in the parahippocampal gyri and greater activation increases in the right hippocampal formation during encoding. Data from this study therefore suggest that children with FAS/PFAS recruited more extensive neural resources to support successful memory encoding during this task. In Study III, I used a behavioral source memory paradigm to investigate higher-order executive processes essential for memory encoding. Despite similar recognition accuracy across all diagnostic groups, participants in the FAS/PFAS group showed impaired memory for source details. This pattern of impairment was only partially mediated by working memory performance. These three studies provide novel clarification of the neural and cognitive mechanisms underlying declarative memory impairments in children with FASD.